Filsafat Islam: Antara Duplikasi dan Kreasi - Abdullah Sattar (Ulumuna, 2010)
Many muslim leaders deal with philosophy, and became a philosopher. Unfortunately, many Orientalists deny their ability to philosophize. Tenneman and Renan is of the orientalists who deny, at least question, the ability of muslim philosophical thinker. There are three reasons they stretcher; first, the Qur'an negates the freedom of thought, secondly, the character of Arabs who can not philosophize; and third, the Arabs are a Semitic which belong to races that have low reasoning power. Meanwhile, another orientalist believes that Islamic philosophy is Islamicised Greek philosophy. This paper tries to elaborate muslim thinkers to address concerns with an intense orientalists on the ability and independence of muslim thinkers in the philosophical. They show that the muslim philosopher is not merely duplicate the philosophy that has been established previously, but its main source of creativity itself through the Qur'an.